PENGARUH SUPERVISI EDUKATIF KOLABORATIF TERHADAP PENINGKATAN KOMPETENSI DAN KINERJA GURU DALAM PENYELENGGARAAN KEGIATAN PEMBELAJARAN - Kholid, Kholid (STAI Darul Qalam Tangerang, 2022)
Supervision is supervision in the field of education carried out by people who have a higher position or position than the person being supervised, in this case it is a teacher. Supervision is also defined as coaching given to all school staff so that they can improve their ability to develop a better learning situation. This study aims to determine the influence of collaborative educational supervision carried out by the head of the madrasah in improving the competence and performance of teachers in the implementation of learning.This research is a school action research that is carried out 2 (two) cycles. The aspects that are the focus of observation and attention to research are matters related to the main task of the teacher in the implementation of learning, namely the teacher's ability to compile learning plans, learning implementation, assessment, and how teachers compile follow-up plans from learning activities and assessment results that have been carried out.The results showed that there was an increase in scores from the aspects mentioned above between cycle 1 and cycle 2. This shows that there is an influence of collaborative educational supervision on improving teacher competence and performance in the implementation of learning.